Pemanfaatan Rimpang Alang-alang (Imperata cylindrica) sebagai Bioherbisida Pra Tumbuh untuk Pengendalian Gulma di Pembibitan Awal Kelapa Sawit - Rufinusta Sinuraya (JURNAL CITRA WIDYA EDUKASI, 2022)
The use of herbicides is a weed control methods in oil palm plantations, will have a negative impact on plants and the environment if used continuously. Imperata cylindrica can be used as a natural bioherbicide because it contains compounds that can inhibit the growth of other plants. This study aims to obtain alternative organic materials as bioherbicides for controlling pre-growing weeds in oil palm early nurseries. The method used was a non-factorial randomized block design (RBD) with P0 (Without Bioherbicide Extract), P1 (1% Extract), P2 (2% Extract) and P3 (3% Extract). The results showed that the rhizome of the alang-alang (Imperata cylindrica) can be used as an alternative material for making bioherbicides for controlling pre-growing weeds in early oil palm nurseries. Provision of alang-alang rhizome extract as a bioherbicide did not show a significant effect on the morphology and physiology of oil palm seedlings. The content of compounds contained in the bioherbicide extract of the pre-growing rhizome of alang-alang consists of flavonoids 0.097% and tannins 0.105%. Provision of alang-alang rhizome bioherbicide extract with an extract concentration of 2% is recommended as a concentration that can be used to reduce weed growth.